The Effect of Different Percentage of Dammar Gum on Water Absorption Performance of Palm Oil Frond Fiber Reinforced Tapioca Starch Composite - Muhammad Izzfaiz; JAMILUDDIN BIN JAAFAR (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The demand for wood and wood-based composites is increasing rapidly due to global economic growth and population rise. This has led to deforestation and global warming, raising sustainability concerns. A major drawback in fiberboard manufacturing is poor water resistance, particularly among coupling agents. Another issue is determining the optimum composition of dammar gum to achieve the best water resistance. This study investigates the effect of varying dammar gum percentages on the water absorption performance of oil palm frond fiber reinforced with tapioca starch. Materials used include oil palm fronds, tapioca starch, and dammar gum in 2%, 4%, 6%, and 8% weight ratios. The process involved crushing, sieving into two fiber size groups, drying, mixing, compression molding, and laser cutting. Water absorption and thickness swelling tests were conducted. DG 6% performed best with the lowest thickness swelling (3% at 5 hours, 20% at 24 hours) and relatively low water absorption (80% at 5 hours, 83% at 24 hours). The control sample, DG 0%, showed the worst performance with thickness swelling up to 74% and water absorption up to 68%. DG 8% showed the best long-term resistance with 31% water absorption and 11% swelling at 504 hours. In conclusion, dammar gum is effective in reducing water absorption, but excessive amounts can cause agglomerates, reducing performance.